AFFECTING FACTORS FOR THE ADOPTION OF CLOUD-BASED ERP SYSTEM IN IRAQI SMES AN EMPIRICAL STUDY - MOHAMMED, GHAITH JAAFAR; Mohd Aboobaider, Burhanuddin; Alyousif, S.; Alkhayyat, A.; Ali, Mohammed H.; Malik, Rami Qays; Jaber, Mustafa Musa (International Federation of Engineering Education Societies (IFEES), 2022)
Cloud-based enterprise resource planning (ERP) and cloud computing are critical requirements for all SMEs since they can be used to facilitate the SMEs’ growth by creating competitive and personalized innovations considering their required business scope. To date, the growth of cloud technologies has led to the development of new systems and applications in many fields and areas including businesses. Our previous study proposed an adoption model to investigate the main determinants and logistical factors that influence decision-makers of SMEs to adopt cloud-based ERP systems. The aim of this research is to enhance the previous work by evaluating and validating the new model in real life to determine whether it has achieved what it was developed for and determine the reliability of the research results. The methodology and results of the evaluation and validation process of the proposed model are presented in this research. Considering there is little documentation in the literature specifically relevant to how proposed models have been evaluated and validated, hence providing this insight will assist both the academic researchers and decision-makers. The evaluation and validation methodology and the model itself contribute toward a better understanding of adoption processes. Furthermore, the evaluation and validation procedure in future work can be used to measure, enhance and determine whether the proposed models can be used in real life.